2005
DOI: 10.1177/0256090920050305
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Marketing in Emerging Economies: Some Lessons for the Future

Abstract: Relationship marketing as a philosophy and a set of practices is now widely accepted by both academics and practitioners. At the centre of the relationship marketing paradigm is the notion that making the most out of existing clients is essential for long-term profitability. Retaining clients by developing relationships with them is crucial to establishing and maintaining a competitive advantage in the market. But, moving away from an analysis of needs to an analysis of the customer, from management of the tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 59 publications
0
22
0
2
Order By: Relevance
“…We situate our research within an emerging marketing context due to paucity of research in emerging markets and dominance of studies published in developed markets. This is surprising given that emerging markets differ from developed markets in terms of economic and sociocultural realities (Flambard‐Ruaud, ). Tahmouresi, Bender, Schmitz, Baleshzar, and Tuschen‐Caffier () demonstrated that emotions differ across cultures and between developed and developing countries.…”
Section: Introductionmentioning
confidence: 99%
“…We situate our research within an emerging marketing context due to paucity of research in emerging markets and dominance of studies published in developed markets. This is surprising given that emerging markets differ from developed markets in terms of economic and sociocultural realities (Flambard‐Ruaud, ). Tahmouresi, Bender, Schmitz, Baleshzar, and Tuschen‐Caffier () demonstrated that emotions differ across cultures and between developed and developing countries.…”
Section: Introductionmentioning
confidence: 99%
“…Também, se refere ao uso de um subconjunto de relações que operam de acordo com normas de reciprocidade podendo apresentar uma conotação negativa quando relacionado ao suborno e à corrupção. Nesse contexto, o guanxi ou guanxixue representa o uso de conexões pessoais para burlar regulamentos, leis ou normas, e assim, obter benefícios políticos e/ou econômicos (GUTHRIE, 1998;FLAMBARD-RUAUD, 2005;LEE & DAWES, 2005;LORD, 2007).…”
Section: Guanxiunclassified
“…A governança interorganizacional utiliza-se de mecanismos que influenciam os custos de transação e fornecem incentivos para as iniciativas de criação de valor, tais como o investimento em ativos específicos à relação, a partilha de conhecimentos ou a combinação de recursos estratégicos complementares (DYER & SINGH, 1998). Ao analisar díades formadas por empresas de países diferentes, deve-se considerar não somente o estabelecimento e a configuração dos mecanismos de governança que operam para garantir o funcionamento contínuo das parcerias (HAHN & GOLD, 2014), mas também a importância relativa dos atributos que compõem o relacionamento, valorados e construídos de modo diferente em diversas partes do mundo (FLAMBARD-RUAUD, 2005). Nesse contexto, os RIOs que envolvem empresas chinesas requerem atenção especial, principalmente no que se refere ao entendimento da construção da confiança e sua inter-relação com o guanxi -entendido como a relação entre várias partes que cooperam juntas e se apoiam umas às outras (YEN & ABOSAG, 2016).…”
Section: Introductionunclassified
“…Hsu et al (2008) observed preserving loyalty of established customer as a crucial contributor to the achievement and profitability of business. Accordingly, the main reason why researchers should consider revisit intention is the fact that "globalization of markets, competitive pressure, brand multiplication and, above all, the ever-changing lifestyles and consumer behavior have forced companies to develop strategies to keep their clients and create consumer loyalty programs" (Flambard-Ruaud, 2005), particularly in tourism industry.…”
Section: Review Of Literaturementioning
confidence: 99%